Reactive scheduling in collaborative supply chain: A literature review (2017)
This paper aims to review the literature on the reprogramming of production in collaborative supply chains, through a thorough investigation and Scientometric analysis to identify the behavior of publications in recent years, which allow the identification of authors, areas Of the knowledge, countries and institutions most unrelated in the area. Finally, research lines are presented with a greater tendency for new research that contributes to the literature and the improvement of stocks. © 2017.